Analysis of the Activity of Nuclear Export Signals Using Fluorescent BSA Conjugates - Carl M. Feldherr; Debra Akin (BioTechniques, 2002)
Here we demonstrate that fluorescein-labeled BSA conjugated with a mixture of nuclear import and export signals can be used to evaluate export activity. The method is based on the assumption that the intracellular distribution of the labeled conjugate [nuclear/cytoplasmic (N/C) fluorescent ratio] is dependent on the relative activity of the import versus the export signals. Using BALB/c cells as a model system, it was shown that this assumption is correct. Thus, the N/C fluorescent ratio increased significantly when an active leucine-rich nuclear export signal was replaced with its inactive mutant form in conjugates that also contained classical nuclear import signals. This approach was then used to demonstrate that the same leucine-rich nuclear export signal, which functions in vertebrates, is also active in amoebae.